To Determine Mean Changes in Intraocular Pressure during Hemodialysis in patients of End Stage Kidney Disease - Salman Mehmood, Muhammad Ahmad, Ijaz Nabi, Nouman Hameed Sheikh, Bilal Javed, Rana Zahid Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine mean changes in intraocular pressure (IOP) during hemodialysis (HD) in patients of chronic renal failure Study design: Descriptive case series Place and duration of study: Department of Nephrology, Allied Hospital, Faisalabad, from 15/06/2016 to 15/09/2016 Methodology: End stage renal patients meeting the inclusion criteria on hemodialysis were included in the study. Written informed consent was obtained. After taking detailed history and clinical examination, intraocular pressure was measured just before and one hour after the initiation of HD using perkin’s hand held tonometer. Results: The mean± SD age of patients was 53.8±8.81. The minimum IOP was 11.20mmHg before hemodialysis and maximum was 16.80mmHg. Mean±SD was 14.08±1.38. Similarly minimum IOP after dialysis was 12 mm Hg and maximum was 19.0mm Hg, with a mean of 15.3. IOP in males before HD was 14.09±1.33. However after dialysis was 15.56±1.7. Thus the change in IOP seen in males was 1.6 ± 0.89 and in females was 14.08±1.46 and after dialysis was 15.13±1.45. Thus the calculated IOP change in females was 1.37±0.98. Chi square value was 2.67. p value observed was 0.263. Conclusion: There is significantly increased IOP during hemodialysis.